Quantitation of Fibrin Deposition and Elimination in Organs of Rats Injected with Labelled Fibrinogen and Albumin - Busch, Christer; Rammer, Lennart; Saldeen, Tom (Thrombosis and Haemostasis, 1973)
A method for quantitation of fiprin deposits in organs of rats, using labelled fibrinogen and albumin, is described. In rats previously injected with 125I-fibrinogen, thrombin was used to induce intravascular deposition of fibrin in various organs. 131I-albumin was injected shortly before sacrifice for determination of the organ plasma volume. The fibrin content of the organ was calculated by subtraction of the plasma and extravascular 125I-radioactivities from the total 125I-content of the organ. The organ plasma radioactivity was obtained as the product of 12 5I in plasma and the organ plasma volume and the extravascular radioactivity as the difference between total and plasma radioactivity in organs of rats before the thrombin infusion. It was found that the method is especially suited for quantitation of fibrin deposition and elimination in the lungs, but it should be also applicable to other organs. In the liver and kidneys certain problems occur which interfere especially with fibrin elimination studies in these organs.